A case report of low grade fetal lung adenocarcinoma with TP53 mutation. Issue 11 (18th March 2022) - Wang, Bo; Jin, Huri
Abstract: Rationale: Fetal lung adenocarcinoma (FLAC) is a rare malignant tumor that occurs in the alveolar epithelium. FLAC, as a distinct entity, is a malignancy with a very low incidence, accounting for less than 0.5% of all lung tumors, with a high rate of misdiagnosis due to its rarity, lack of typical presentation and imaging signs. According to histopathological differences, FLAC is further divided into 2 types: low-grade FLAC and high-grade FLAC. In the article, we report a young woman who was diagnosed with low-grade fetal-type lung adenocarcinoma. Patient concerns: An 18-year-old female patient was admitted due to cough and chest distress. Diagnosis: The final pathological examination confirmed that the lesion was a low-grade fetal lung adenocarcinoma. Interventions: The patient underwent thoracoscopic left lower lobectomy and regional lymph node dissection. Outcomes: The postoperative course was stable, and no recurrence was observed 1 year after operation. Lessons: To the best of our knowledge, there are no previous case reports of low-grade fetal-type adenocarcinoma, TP53 gene mutation, and the significance of its mutation is not extensively studies. FLAC, although extremely rare, is considered in the differential diagnosis of lung cancer. In addition, biopsy, histopathology, and specific immunohistochemical staining of larger tissue specimens are helpful for accurate diagnosis of FLAC.